2014
DOI: 10.1016/j.neuint.2013.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Antagonist-induced conformational changes in dopamine transporter extracellular loop two involve residues in a potential salt bridge

Abstract: Ligand-induced changes in the conformation of extracellular loop (EL) 2 in the rat (r) dopamine transporter (DAT) were examined using limited proteolysis with endoproteinase Asp-N and detection of cleavage products by epitope-specific immunoblotting. The principle N-terminal fragment produced by Asp-N was a 19 kDa peptide likely derived by proteolysis of EL2 residue D174, which is present just past the extracellular end of TM3. Production of this fragment was significantly decreased by binding of cocaine and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 71 publications
0
6
0
Order By: Relevance
“…Previous structure-based studies of DAT-substrate/drug interactions used LeuT, which shares 22% sequence identity with hDAT, as template. Despite the low sequence similarity, the conservation of the fold and local packing geometry near the substrate-binding site permitted to gain insights into DAT conformational changes involved in cocaine binding and DA translocation ( 13 , 18 20 , 65 69 ). Here, for the first time, we used as template, the recently resolved dDAT structure ( 33 ), which shares >50% sequence identity with hDAT, and we modeled the EL2 loop unresolved in the fruit fly orthologs using as constraint data from previous cross-linking studies ( 16 , 47 ) (Figure 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous structure-based studies of DAT-substrate/drug interactions used LeuT, which shares 22% sequence identity with hDAT, as template. Despite the low sequence similarity, the conservation of the fold and local packing geometry near the substrate-binding site permitted to gain insights into DAT conformational changes involved in cocaine binding and DA translocation ( 13 , 18 20 , 65 69 ). Here, for the first time, we used as template, the recently resolved dDAT structure ( 33 ), which shares >50% sequence identity with hDAT, and we modeled the EL2 loop unresolved in the fruit fly orthologs using as constraint data from previous cross-linking studies ( 16 , 47 ) (Figure 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of the substrate (apo state), Na 1 -coupled transporters of the SLC6 fold are stabilized in the outwardfacing open conformation Gaffaney et al, 2014;Kazmier et al, 2014;Malinauskaite et al, 2014;Sandtner et al, 2014). Thus, prior to 5-HT application, the cell-surface population of hSERT is dominated by this apo state, whereas during 5-HT application, the transporter population becomes engaged in transport, adopting all potential conformational states of the alternating access cycle.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, it is poorly understood how drugs affect the overall conformational behavior of SERT. Current insight into mammalian SLC6 transporter conformations stabilized by drugs is mainly based on biochemical approaches, such as cysteine accessibility or protease and alkylation protection analyses (Zhang and Rudnick, 2006;Jacobs et al, 2007;Tavoulari et al, 2009;Koldso et al, 2013;Gaffaney et al, 2014) that do not offer direct experimental information on specific intraprotein motions occurring during drug binding. Studies of protein dynamics in purified bacterial SLC6 homologs using Förster resonance energy transfer and electron paramagnetic resonance spectroscopy techniques have identified specific motions associated with alternating access (Kazmier et al, 2014;Kohut et al, 2014); however, these techniques have not been available to study mammalian transporters.…”
Section: Introductionmentioning
confidence: 99%
“…Another factor that may contribute to role of the DAT N terminus in substrate/inhibitor affinities is the interaction of the DAT N terminus with PIP 2 and intracellular loop 4 (34, 47). A recent molecular dynamics study examining the hDAT N terminus on the dDAT background reported a PIP 2 -mediated interaction with hDAT N-terminal residues (Lys 3 , Lys 5 , and Arg 51 ) with intracellular loop 4 (34). This interaction appears to break salt bridges necessary for the conserved intracellular gate.…”
Section: Wt Sert N-dat/sert Sert/c-dat Dat/sert/datmentioning
confidence: 98%
“…Determining how these drugs interact with their molecular targets is essential for understanding psychostimulant addiction, as well as psychiatric treatment. The monoamine transporters DAT 2 and SERT are the primary targets for a variety of psychostimulants, such as cocaine and amphetamines (AMPH, methamphetamine, and 3,4-methylenedioxymethamphetamine), as well as the SSRI and norepinephrine-dopamine reuptake inhibitor classes of antidepressants (1)(2)(3)5). Cocaine and SSRI/norepinephrine-dopamine reuptake inhibitors inhibit these transporters by directly blocking DA and 5HT reuptake, whereas amphetamine and its congeners are competitive DAT and SERT substrates.…”
mentioning
confidence: 99%